Philosophers and Theologians on the Freedom of the Will - Baillie, D. M. (Scottish journal of theology, 1951)
It is a curious fact that while the problem of free will has been long and widely discussed by both philosophers and theologians in the modern world, it has been largely in two separate compartments, the one set seldom conferring with the other, or even overhearing what the other has to say. Sometimes they seem almost to be talking of two different things.